Maximizing Culinary Business Profit with the POM-QM Simplex Method - Fredy; Kevin; Limba Jaya, Sartito; Angie, Supenatus; Ramayani, Nadia; Effendy, Dudy (Inovasi Analisis Data, 2024)
Optimizing profit in Micro, Small, and Medium Enterprises (MSMEs) poses a common challenge for owners, particularly in the culinary sector. This study explores the potential application of the simplex method to maximize profits in